1998
DOI: 10.1038/eye.1998.224
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and plasma fibronectin in the aqueous humour of primary open-angle glaucoma, exfoliative glaucoma and cataract patients

Abstract: 886Cell u lar and plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
0
21
0
4
Order By: Relevance
“…Although fibronectin is considered a minor to insignificant component of the adult lens [4,5,8,11], Babizhayev and Brodskaya reported changes of fibronectin staining in human lens sections in correlation to human aging and cataract development [2]. Different fibronectin concentrations have been measured in aqueous humor of patients before glaucoma or cataract surgery, indicating a disruption of the blood-aqueous barrier in glaucomatous eyes [16]. Immunohistochemical studies revealed proteinacous deposits containing fibronectin within the capsular bag and on the surfaces of explanted IOLs [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Although fibronectin is considered a minor to insignificant component of the adult lens [4,5,8,11], Babizhayev and Brodskaya reported changes of fibronectin staining in human lens sections in correlation to human aging and cataract development [2]. Different fibronectin concentrations have been measured in aqueous humor of patients before glaucoma or cataract surgery, indicating a disruption of the blood-aqueous barrier in glaucomatous eyes [16]. Immunohistochemical studies revealed proteinacous deposits containing fibronectin within the capsular bag and on the surfaces of explanted IOLs [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…non-pigmented ciliary epithelium, iris pigment epithelium, lens epithelium, trabecular meshwork, and vascular endothelia of the iris, are bathed by the aqueous humor. Further changes in aqueous protein concentrations (Ku È chle et al, 1994) as well as aqueous levels of a1-lipoprotein and ceruloplasmin (Baba, 1982), transferrin (Koliakos et al, 1996), and ®bronectin (Vesaluoma et al, 1998) have been reported in the PEX syndrome and may contribute to its pathogenesis.…”
Section: Tgf-b In Aqueous Humormentioning
confidence: 95%
“…В нескольких исследованиях обнаружена бо-лее высокая концентрация фибронектина в жид-кости передней камеры глаза пациентов с глау-комой [51,82], причём при псевдоэксфолиативной глаукоме уровень этого гликопротеина значитель-но выше, чем при ПОУГ. Авторы связывают это с повреждением и нарушенной проницаемостью гематоофтальмического барьера [82].…”
Section: ) глаукомаunclassified
“…Авторы связывают это с повреждением и нарушенной проницаемостью гематоофтальмического барьера [82]. В другом исследовании был определён более высокий уро-вень фибронектина в жидкости передней камеры пациентов с псевдоэксфолиативным синдромом (ПЭС) (без подтверждённого диагноза «глауко-ма»), чем без него [55].…”
Section: ) глаукомаunclassified